Construction of Metal–Organic Framework Films via Crosslinking‐Induced Assembly. Issue 9 (1st January 2023) - Li, Hongfeng; Shi, Haohao; Chen, Xinyi; Ren, Zhen; Shen, Yu; Wu, Peng; Fan, Yun; Zhang, Xinglong; Shi, Wenxiong; Liao, Honggang; Zhang, Suoying; Zhang, Weina; et al.
Abstract: The construction of metal–organic framework (MOF) films is a crucial step for integrating them into technical applications. However, due to the crystallization nature, it is difficult to grow most MOFs spontaneously or process them into films. Here, a convenient strategy is demonstrated for constructing MOF films by using modulators to achieve homogeneous assembly of MOF clusters. Small clusters in the early growth steps of MOFs can be stabilized by modulators to form fluidic precursors with good processibility. Then, simple removal of modulators will trigger the crosslinking of MOF clusters and lead to the formation of continuous films. This strategy is universal for the fabrication of several types of MOF films with large scale and controllable thickness, which can be deposited on a variety of substrates as well as can be patterned in micro/nano resolution. Additionally, versatile composite MOF films can be easily synthesized by introducing functional materials during the crosslinking process, which brings them broader application prospects. Abstract : Small clusters in the early growth steps of metal–organic frameworks (MOFs) can be stabilized by modulators to form fluidic precursors (denoted as preMOFs) with good processibility. Then, the removal of solvents and modulators will trigger the crosslinking of preMOFs and lead to the formation of continuous MOF films.